Acute thermal stress alters sperm swimming activity, viability, and gene expression in blue catfish, Ictalurus furcatus - Kaylan M. Price; Brian G. Bosworth; Samitha S.N. Liyanage; Jason W. Abernathy; Benjamin H. Beck; Luke A. Roy; Timothy J. Bruce; Rex A. Dunham; Ian A.E. Butts (Theriogenology, 2026)

Interactive influence of dietary protein levels and daily differential meal allocation on the growth performance of tilapia hybrid (Oreochromis mossambicus × O. niloticus) reared in seawater culture system - Cezarie L. Golingay; Rex Ferdinand M. Traifalgar; Vyenge Erre D. Gayosa; Mary Jessa Bell B. Pagapulan (Animal Feed Science and Technology, 2026)

Agricultural methane emissions and non-communicable disease mortality in West Africa: an ecological panel study of the climate-health nexus, 2015–2020 - Amadou Barrow; Lamin M. Ceesay; Elizabeth O. Oloruntoba; Rex A. Kuye (Environmental Monitoring and Assessment, 2026)

A sustainable dietary protein source, Gracilariopsis heteroclada protein concentrate, as a replacement for soybean meal in the diets of black tiger shrimp Penaeus monodon postlarvae - Carl John M. Saromines; Rex Ferdinand M. Traifalgar; Janice A. Ragaza; Mary Jessa Bell B. Pagapulan; Vyenge Erre D. Gayosa (Journal of Applied Phycology, 2026)

Correction: A meta-analysis on the effects of temperature and salinity on Scylla spp. larvae - Justine T. Gevana; Fredson H. Huervana; Mark Henry F. De Leon; Ivy S. Arizapa; Alan N. Failaman; Rex Ferdinand M. Traifalgar (Frontiers in Marine Science, 2026)

Melt-bearing nodules from Tenerife reveal magma reservoir diversity prior to caldera-forming eruptions - Emma L Horn; Rex N Taylor; Thomas M Gernon; Michael J Stock; Katherine E Schofield; Richard J. Brown; Victoria C Smith; Danielle McLean (Contributions to Mineralogy and Petrology, 2026)
Partially crystalline nodules are occasionally discovered within breccias linked to large ignimbrite-forming eruptions, providing evidence of the fragmentation of the plutonic reservoir and conduit system during such eruptions. These nodules offer valuable insights into the magmatic systems fuelling these highly explosive volcanoes. On Tenerife, crystal-rich samples containing interstitial melt are preserved in several Plinian eruption deposits spanning over ~ 1.8 million years, but the crustal architecture and interactions between magma reservoirs beneath the island remain poorly understood. This study focuses on explosively fragmented juvenile nodules from Tenerife’s pyroclastic deposits, which provide snapshots of the mush reservoir preceding caldera-forming events. Petrological, major element and trace element analyses were conducted on juvenile nodules from five major caldera-forming eruptions: Caleta (221 ka), Fasnia (312 ka), San Juan (1.50 Ma), Morteros (~ 1.70 Ma), and Gaviotas (1.84 Ma). These nodules preserve a range of crystallisation stages within Tenerife’s alkaline magmatic system, uniquely containing interstitial groundmass that existed in a supra-solidus state at the time of eruption, with an average melt content of ~ 25 vol%. Despite macro-mineralogical variability between eruptions, the juvenile nodules exhibit consistent basanite interstitial groundmass chemistry and lithologies, suggest that the mafic mush reservoir beneath Tenerife has remained both chemically and petrologically stable over ~ 1.8 million years. This study provides a new perspective on the stability of the mafic mush reservoir beneath Tenerife, highlighting its persistent role in the volcano’s magmatic plumbing system. The chemical consistency of the mush contrasts with the episodic mobilisation and more chemically diverse evolved phonolite melts, underscoring the importance of understanding mid-crustal processes leading to explosive eruptions. These findings provide evidence for a long-lived, stable mush reservoir and a new perspective on the compositional makeup of the crystal-mush reservoirs at defined points in time, enhancing our temporal understanding of ocean island volcanoes and their crustal magma mush reservoirs.

A meta-analysis on the effects of temperature and salinity on Scylla spp. larvae - Justine T. Gevana; Fredson H. Huervana; Mark Henry F. De Leon; Ivy S. Arizapa; Alan N. Failaman; Rex Ferdinand M. Traifalgar (Frontiers in Marine Science, 2026)
Mangrove crabs ( Scylla spp.) are recognized as economically valuable and important crustaceans in the aquaculture industry. This includes S. olivacea , S. paramamosain , S. tranquebarica, and S. serrata . However, aquaculture production of these species continues to depend on wild-caught seedstock due to the low success rates of hatchery operations. This highlights the need to explore alternative Scylla species to reduce pressure on wild populations. Moreover, further improvements in hatchery management techniques for larval rearing are necessary, building on the foundation established by previous studies. Accordingly, this study evaluates the effects of water temperature and salinity on the survival of S. olivacea, S. paramamosain, S. tranquebarica and S. serrata larvae through meta-analysis. A search strategy following PRISMA guidelines was used, and the literature search involved ScienceDirect, Google Scholar, Scopus, and Wiley Online Library. A total of 321 studies were determined for S. olivacea , 657 for S. paramamosain , 551 for S. tranquebarica , and 969 for S. serrata . Further screening resulted in 6 articles for S. olivacea , 8 for S. paramamosain , 7 for S. tranquebarica and 7 for S. serrata . From these, 4 articles for S. olivacea , 6 for S. paramamosain , 5 for S. tranquebarica , and 4 for S. serrata were included for meta-analysis and meta-regression using R. Results showed that temperature has a mild effect, while salinity has a greater effect on the survival of mangrove crab larvae. It is then suggested that the temperature levels should be 30 °C for S. olivacea , 28–30 °C for S. paramamosain , 30.5 °C for S. tranquebarica , and 29 °C for S. serrata . Similarly, the salinity levels should be 30 ppt for S. olivacea , 28–31 ppt for S. paramamosain , 31 ppt for S. tranquebarica , and 28–33 ppt for S. serrata . Moreover, high confidence intervals and heterogeneity were observed across all species, which may be attributed to the limited number of studies and differences in sampling size and experimental design. These findings are essential for developing optimized and standardized larval rearing protocols to enhance hatchery production and reduce reliance on wild stocks.

Dietary supplementation of Durvillaea potatorum fucoidan enhances the immune responses and improves survival of juvenile black tiger shrimp Penaeus monodon against white spot syndrome virus and acute hepatopancreatic necrosis disease - Joseph P. Faisan; Rex Ferdinand M. Traifalgar; Leobert D. de la Peña; Valeriano L. Corre; Mary Jessa Bell B. Pagapulan; Vyenge Erre D. Gayosa (Aquaculture International, 2026)

Fermentation of rice milling by-products can completely replace soybean meal in the diet of Oreochromis niloticus fingerlings - Mark Henry F. De Leon; Dinah Grace D. Bienes; Mary Jessa Bell B. Pagapulan; Emelyn Joy G. Mameloco; Vyenge Erre D. Gayosa; Fredson H. Huervana; Carmelo S. del Castillo; Rex Ferdinand M. Traifalgar (Frontiers in Marine Science, 2026)
The expansion and intensification of aquaculture have been widely adopted to support large-scale production, creating a reliance on high-protein feed ingredients such as soybean meal (SBM) and fish meal (FM). These ingredients, however, are costly and unsustainable, emphasizing the need for alternative plant-based protein sources for aquafeeds. This study assessed the nutritional and feed value of fermented rice bran meal (FRBM) as a substitute for SBM in the diet of tilapia ( Oreochromis niloticus ) fingerlings. Five diets were formulated with FRBM replacing SBM at 0%, 25%, 50%, 75%, and 100%, and were fed to fingerlings over a 60-day period. Results showed that FRBM could fully replace SBM, with growth-promoting effects particularly observed at 25% replacement. Survival, percentage weight gain, feed conversion ratio (FCR), and specific growth rate (SGR) did not differ significantly among the treatments with varying FRBM levels. No significant differences in carcass composition (protein, lipid, and ash) were observed among tilapia fed with diets containing FRBM replacement. The apparent protein and dry matter digestibility coefficients of FRBM are 91.52% and 66.67%, respectively. Histological examination also revealed no intestinal abnormalities, even at the highest level of FRBM inclusion. Overall, the findings suggest that solid-state fermented rice bran can fully replace soybean meal in the diet of O. niloticus . In addition, its use presents a practical option to help meet the growing protein requirements in aquafeeds and to promote the sustainable expansion of tilapia aquaculture.

Real-Time Acoustic Telemetry Buoys as Tools for Nearshore Monitoring and Management - James M. Anderson; Brian S. Stirling; Patrick T. Rex; Emily A. Spurgeon; Anthony McGinnis; Zachariah S. Merson; Darnell Gadberry; Christopher G. Lowe (Journal of Marine Science and Engineering, 2026)
Acoustic telemetry monitoring for tagged sharks in nearshore waters has become an important tool for beach safety management; however, detection performance can vary widely in shallow, high-energy nearshore environments where management decisions are often most time-sensitive. Real-time acoustic telemetry buoys offer the potential to deliver live detections and system diagnostics, but their performance relative to autonomous bottom-mounted receivers remains poorly evaluated under realistic coastal conditions. We compared the detection efficiency of real-time buoy-mounted acoustic receivers and autonomous bottom-mounted receivers across five nearshore sites in southern California. Using paired long-term reference tag deployments and short-term range tests, we quantified detection probability, effective detection range, and the influence of environmental conditions and receiver placement. Detection performance was evaluated in relation to wind speed, water temperature, receiver tilt, and signal-to-noise ratio. Both buoy-mounted and bottom-mounted receivers maintained high long-term detection efficiency, recovering 77–99% of expected transmissions at 82–250 m. Range tests indicated greater effective detection distances for buoy-mounted receivers, with 50% detection probabilities occurring at approximately 471 m compared to 282 m for bottom-mounted receivers. Receiver placement strongly influenced performance, with surface-mounted receivers outperforming bottom-mounted units regardless of receiver model. Environmental effects on detections were site-specific and variable. Detection probability varied predictably with environmental conditions. Higher SNR increased detection success, particularly for bottom/substrate mounted receivers, while warm water significantly reduced detection probability across placement configuration. These results demonstrate that real-time acoustic telemetry buoys provide reliable detection performance in dynamic nearshore environments while offering key operational advantages, including immediate data access and system diagnostics. The observed relationships demonstrate that receiver performance is dynamic rather than fixed, and that real-time buoy systems therefore represent a practical tool for coastal monitoring programs that require timely information to support adaptive management, public safety, and conservation decision making.

Dietary crude ulvan from Ulva intestinalis enhances growth, salinity stress tolerance, and immunity against Vibrio harveyi in early juvenile milkfish Chanos chanos - Vyenge Erre D. Gayosa; Rex Ferdinand M. Traifalgar; Lovelyn Marie Nievales-Naluaran; Mark Henry F. De Leon (Algal Research, 2025)

P30-81 High-throughput RNA sequencing (Transcriptomics) combined with multiparametric New Approach Methodologies (NAMs) for cardiotoxicity risk assessment and mechanistic determination - J. Eakins; C. Bruhn; A. Rosell-Hildago; R. Rex; D. Yuezak; M. Fernandes dos Reis; T. Samatov; A. Hackmann; G.R. Aquino; C. Vogeley; N. Sahini; G. Goussarov; et al. (Toxicology Letters, 2025)

Colloidal Nafion morphology in 1,2-alkanediols and its impact on membrane and ionomer properties - Jeffrey M. Klein; Danah Kim; Cynthia Welch; Rex P. Hjelm; Marilyn E. Hawley; Anna Sokolova; Sung-Dae Yim; Natalia Macauley; Hui Xu; Sara Pedram; Jasna Jankovic; Seung Geol Lee; et al. (Chemical Engineering Journal, 2025)

Zinc manganese oxide spinel phase nanomaterial layered on solar stills applications: An analytical study for improved performance compared with machine learning methods - V. Ramesh Srenyvasan; S. Muthuvel; M. Kalil Rahiman; S. Sudheer Khan; Prathiba Rex (Journal of Water Process Engineering, 2025)

eDNA metabarcoding detection of nearshore juvenile white sharks (Carcharodon carcharias) and prey fish communities - Zachariah S. Merson; Elizabeth E. Jahn; Matthew A. Barnes; Emily A. Spurgeon; Patrick T. Rex; Jack T. Elstner; Yamilla N. Samara Chacon; James M. Anderson; Whitney D. Jones; Christopher G. Lowe (Journal of Experimental Marine Biology and Ecology, 2025)

Real-time acoustic monitoring facilitates the proactive management of biological invasions - Connor M. Wood; Felix Günther; Angela Rex; Daniel F. Hofstadter; Hendrik Reers; Stefan Kahl; M. Zachariah Peery; Holger Klinck (Biological Invasions, 2024)

P06-21 Multiparametric in vitro assays combined with high-throughput RNA sequencing for cardiotoxicity risk assessment and mechanistic insight - S. Llewellyn; A. Rosell-Hidalgo; C. Bruhn; K. Headspith; T. Samatov; A. Hackmann; G.R. Aquino; M. Fernandes dos Reis; R. Rex; D. Yuezak; C. Vogeley; N. Sahini; et al. (Toxicology Letters, 2024)

Synergistic influence of hydrolyzed squid processing by-products and Bacillus probiotics as dietary supplements on growth performance, immunological responses, and gut health of juvenile black tiger shrimp fed fishmeal-free diets - Maila V. Pan; Victor Marco Emmanuel N. Ferriols; Rex Ferdinand M. Traifalgar (Aquaculture International, 2024)

Solid-state fermentation converts rice bran into a high-protein feed ingredient for Penaeus monodon - Fredson H. Huervana; Rex Ferdinand M. Traifalgar; Cleresa S. Dionela (Frontiers in Marine Science, 2024)
Fermented rice bran (FRB) was evaluated as an alternative protein source to soybean meal (SM) in practical diets for juvenile black tiger shrimp, Penaeus monodon . This feed ingredient was tested in a feeding trial to replace soybean meal in P. monodon diets at 0% (T0), 12.5% (T12.5), 25% (T25), 37.5% (T37.5), and 50% (T50). Five iso-nitrogenous and iso-caloric experimental diets containing 44% crude protein were fed to groups of juvenile shrimp (0.47 ± 0.002 g) randomly assigned to twenty 60-l rectangular tanks equipped with a recirculating seawater system. Each dietary treatment was run in 4 replicates, and the feeding trial lasted 50 days. Results show significant improvement in weight gain, specific growth rate, and protein efficiency ratio in treatment T12.5 and T25. Treatments with higher levels of SM replacement with FRB exhibited similar growth indices to those of the control group. Polynomial regression analysis indicates that the optimum replacement of soybean meal with FRB for optimum growth is 21.08%. The apparent dry matter and protein digestibility coefficients of FRB are 83.05 ± 0.02% and 87.20 ± 0.30%, respectively. There were no significant differences in the whole-body composition (dry matter, protein, lipid, ash) among treatments of shrimp fed with FRB replacement. The data suggest that FRB replacement of dietary soybean meal is feasible at 50% without affecting the growth performance but may promote growth at 21.08% replacement of P. monodon .

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

The comparative effects of visible light and UV-A radiation on the combined toxicity of P25 TiO2 nanoparticles and polystyrene microplastics on Chlorella sp. - Camil Rex M; Amitava Mukherjee (Environmental Science and Pollution Research, 2023)

Magmatic evolution during proto-oceanic rifting at Alu, Dalafilla and Borale Volcanoes (Afar) determined by trace element and Sr-Nd-Pb isotope geochemistry - Emma J. Watts; Thomas M. Gernon; Rex N. Taylor; Derek Keir; Carolina Pagli (Lithos, 2023)

Evidence of increasing juvenile white sharks ' ( Carcharodon carcharias ) habitat use at the Northern Channel Islands - Ryan M. Freedman; James M. Anderson; Chris Caldow; Brian Stirling; Patrick Rex; Emily Spurgeon; Steve McCullough; Kady Lyons; Jack May; Connor F. White; Ryan K. Logan; Emily Meese; et al. (Journal of Fish Biology, 2023)
Juvenile white sharks ( Carcharodon carcharias ) typically aggregate along coastal beaches; however, high levels of recruitment and shifting oceanographic conditions may be causing habitat use expansions. Telemetry data indicate increased habitat use at the Northern Channel Islands (California, USA) by juvenile white shark that may be in response to increased population density at aggregation locations, or anomalous oceanographic events that impact habitat use or expand available habitat. Findings illustrate the need for long‐term movement monitoring and understanding drivers of habitat use shifts and expansion to improve ecosystem management.

Reproductive quality evaluation of male Indian white prawn Penaeus indicus broodstock fed diets supplemented with polychaete extracts ( Marphysa sp.) - Sheryll S. Santander-Avanceña; Rex Ferdinand M. Traifalgar; Erish G. Estante-Superio; Steve P. Janagap; Roger Edward P. Mamauag; Harold M. Monteclaro; Liberato V. Laureta; Gerald F. Quinitio (Invertebrate Reproduction & Development, 2023)

The spatial and volcanic evolution of Ayelu, Abida and Yangudi volcanoes in the Northern Main Ethiopian Rift – Southern Afar, Ethiopia - Rhiannon Rees; Thomas M. Gernon; Derek Keir; Rex N. Taylor; Carolina Pagli (Journal of Volcanology and Geothermal Research, 2023)

Engineered Nanoparticles (ENPs) in the Aquatic Environment: an Overview of Their Fate and Transformations - Camil Rex M; Shalini Anand; Pramod Kumar Rai; Amitava Mukherjee (Water, Air, & Soil Pollution, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Towards production of genome‐edited aquaculture species - Eric M. Hallerman; Rex Dunham; Ross D. Houston; Mark Walton; Anna Wargelius; Diane Wray‐Cahen (Reviews in Aquaculture, 2023)

Dissecting the impact of environment, season and genotype on blackcurrant fruit quality traits - Delphine M. Pott; Sara Durán-Soria; J. William Allwood; Simon Pont; Sandra L. Gordon; Nikki Jennings; Ceri Austin; Derek Stewart; Rex M. Brennan; Agnieszka Masny; Anita Sønsteby; Erika Krüger; et al. (Food Chemistry, 2023)

A revision of the British chronostratigraphy within the last glacial-interglacial cycle based on new evidence from Arclid, Cheshire UK - C.L. Rex; M.D. Bateman; P.C. Buckland; E. Panagiotakopulu; S.J. Livingstone; M. Hardiman; L. Eddey (Quaternary Science Reviews, 2023)

FKBP5 intron 7 methylation is associated with higher anxiety proneness and smaller right thalamus volume in adolescents - Jacqueline S. Womersley; Simone Roeh; Lindi Martin; Fatima Ahmed-Leitao; Susann Sauer; Monika Rex-Haffner; Sian M. J. Hemmings; Elisabeth B. Binder; Soraya Seedat (Brain Structure and Function, 2022)

Improved Growth and High Inheritance of Melanocortin-4 Receptor (mc4r) Mutation in CRISPR/Cas-9 Gene-Edited Channel Catfish, Ictalurus punctatus - Michael Coogan; Veronica Alston; Baofeng Su; Karim Khalil; Ahmed Elaswad; Mohd Khan; Andrew Johnson; De Xing; Shangjia Li; Jinhai Wang; Rhoda M. C. Simora; Cuiyu Lu; et al. (Marine Biotechnology, 2022)

Observations of a species‐record deep dive by a central Pacific female scalloped hammerhead shark ( Sphyrna lewini ) - James M. Anderson; Patrick T. Rex; Kelsey Maloney; Mark Johnston; Deron Verbeck; Neil Allen; Kim Holland (Journal of Fish Biology, 2022)
A female scalloped hammerhead shark ( Sphyrna lewini ) conducted a species record deep dive to 1240 m in coastal‐pelagic waters off Hawaii Island. This extends the deepest known depth range of the species by over 200 m (650 ft) and highlights the question of the extent to which deep‐diving activity is mediated by physiological constraints, such as temperature and oxygen availability.

Spatiotemporal Patterns in the Biomass of Drift Macroalgae in the Indian River Lagoon, Florida, United States - Lauren M. Hall; Lori J. Morris; Robert H. Chamberlain; M. Dennis Hanisak; Robert W. Virnstein; Richard Paperno; Bernhard Riegl; L. Rex Ellis; Ali Simpson; Charles A. Jacoby (Frontiers in Marine Science, 2022)
Drift macroalgae plays key roles in the ecology of many coastal systems, including the Indian River Lagoon. In the lagoon, changes in the biomass of drift macroalgae may have interacted with an unprecedented bloom of phytoplankton in 2011. Patterns in the biomass of drift macroalgae were identified using new and original analyses of data from several sampling programs collected between 1997 and 2019. All available data show a relatively low biomass of drift macroalgae in 2010–2012, and surveys of fixed transects and seining as part of a fisheries independent monitoring program also recorded low biomass in 2016. Low light availability and potentially stressful temperatures appeared to be the main influences as indicated by the results of incubations in tanks to determine environmental tolerances and data on ambient conditions. Decreased biomass of drift macroalgae had implications for cycling of nutrients because carbon, nitrogen, and phosphorus not stored in the tissues of drift macroalgae became available for uptake by other primary producers, including phytoplankton. The estimated 14–18% increases in concentrations of these elements in the IRL could have promoted longer and more intense phytoplankton blooms, which would have reduced light availability and increased stress on algae and seagrasses. An improved understanding of such feedback and the ecological roles played by drift macroalgae will support more effective management of nutrient loads and the system by accounting for cycling of nutrients among primary producers.

Fine‐scale phylogeography of coastal fishes in the South China Sea: Possible roles of biological traits and geography - Nozomu Muto; Ryo Kakioka; Mazlan Abd Ghaffar; Nguyen Van Quan; Veera Vilasri; Rex F. M. Traifalgar; Ricardo P. Babaran; Fumihito Muto; Hirohiko Takeshima; Hiroyuki Motomura; Satoshi Ishikawa (Journal of Biogeography, 2021)
Aim Although the underlying biotic and abiotic factors of phylogeographic patterns is an important topic in biogeography, they remain largely unexplored in marine fishes. We empirically investigated the effects of several biological traits on phylogeographic patterns of selected marine fishes. We predict that overall similarity in these traits correlates with similarity in phylogeographic patterns among species, and that genetic diversity and demographic stability are associated with these traits, as well as the local (paleo)environment. Location Five localities in the South China Sea (SCS). Taxon Thirteen species of coastal marine fishes. Methods Phylogeographic Concordance Factors (PCFs) based on mitochondrial DNA sequences were tested for correlation with similarity based on distribution range, depth of occurrence, habitat preference, salinity tolerance and fecundity among the subset of the focal species. The relationship between phylogeographic patterns and these traits was also qualitatively examined. Bayesian model averaging was used to test the association between these traits and the genetic diversity estimates. Results Pairwise PCFs of five species across all localities were correlated with pairwise biological similarity, with depth and distribution ranges contributing most to the biological similarity. Nucleotide diversity of Indo‐west Pacific species tended to be greater than that of circumtropical species. Populations showing signs of demographic expansions were concentrated in three localities. A novel concordant population break across six focal species and other marine organisms coincided with the dispersal barrier previously suggested by biophysical dispersal modelling. Main conclusions Abiotic factors were dominant in controlling phylogeographic patterns, with possible contributions from biotic factors. Depth and distribution ranges, or other eco‐physiological traits underlying these, might have influenced the phylogeographic patterns of several species, presumably coupled with historical vicariance. The geography of local populations relative to the shallow continental shelf may explain the heterogeneous demography. Historical vicariance and contemporary ocean currents have contributed to the concordant population break.

Non-random Co-occurrence of Juvenile White Sharks (Carcharodon carcharias) at Seasonal Aggregation Sites in Southern California - James M. Anderson; Alyssa J. Clevenstine; Brian S. Stirling; Echelle S. Burns; Emily N. Meese; Connor F. White; Ryan K. Logan; John O’Sullivan; Patrick T. Rex; Jack May; Kady Lyons; Chuck Winkler; et al. (Frontiers in Marine Science, 2021)
Many terrestrial and aquatic taxa are known to form periodic aggregations, whether across life history or solely during specific life stages, that are generally governed by the availability and distribution of resources. Associations between individuals during such aggregation events are considered random and not driven by social attraction or underlying community structure. White sharks ( Carcharodon carcharias ) have been described as a species that exhibits resource-driven aggregative behaviors across ontogenetic stages and juvenile white sharks are known to form aggregations at specific nursery sites where individuals may remain for extended periods of time in the presence of other individuals. We hypothesized juvenile white sharks form distinct communities during these critical early phases of ontogeny and discuss how a tendency to co-occur across life stages may be seeded by the formation of these communities in early ontogeny. We present results from a series of social network analyses of 86 juvenile white sharks derived from 6 years of passive acoustic telemetry data in southern California, demonstrating the likelihood of association of tagged juvenile white sharks is greater when sharks are of similar size-classes. Individuals in observed networks exhibited behaviors that best approximated fission-fusion dynamics with spatiotemporally unstable group membership. These results provide evidence of possible non-resource driven co-occurrence and community structure in juvenile white sharks during early life stages.

When hazard avoidance is not an option: lessons learned from monitoring the postdisaster Oso landslide, USA - Mark E. Reid; Jonathan W. Godt; Richard G. LaHusen; Stephen L. Slaughter; Thomas C. Badger; Brian D. Collins; William H. Schulz; Rex L. Baum; Jeffrey A. Coe; Edwin L. Harp; Kevin M. Schmidt; Richard M. Iverson; et al. (Landslides, 2021)
On 22 March 2014, a massive, catastrophic landslide occurred near Oso, Washington, USA, sweeping more than 1 km across the adjacent valley flats and killing 43 people. For the following 5 weeks, hundreds of workers engaged in an exhaustive search, rescue, and recovery effort directly in the landslide runout path. These workers could not avoid the risks posed by additional large-scale slope collapses. In an effort to ensure worker safety, multiple agencies cooperated to swiftly deploy a monitoring and alerting system consisting of sensors, automated data processing and web-based display, along with defined communication protocols and clear calls to action for emergency management and search personnel. Guided by the principle that an accelerating landslide poses a greater threat than a steadily moving or stationary mass, the system was designed to detect ground motion and vibration using complementary monitoring techniques. Near real-time information was provided by continuous GPS, seismometers/geophones, and extensometers. This information was augmented by repeat-assessment techniques such as terrestrial and aerial laser scanning and time-lapse photography. Fortunately, no major additional landsliding occurred. However, we did detect small headscarp failures as well as slow movement of the remaining landslide mass with the monitoring system. This was an exceptional response situation and the lessons learned are applicable to other landslide disaster crises. They underscore the need for cogent landslide expertise and ready-to-deploy monitoring equipment, the value of using redundant monitoring techniques with distinct goals, the benefit of clearly defined communication protocols, and the importance of continued research into forecasting landslide behavior to allow timely warning.

Development and spatial application of a submerged aquatic vegetation model for Cootes Paradise Marsh, Ontario, Canada - Rex W. K. Tang; Susan E. Doka; Jonathan D. Midwood; Jesse M. Gardner Costa (Aquatic Sciences, 2021)

Landslides across the USA: occurrence, susceptibility, and data limitations - Benjamin B. Mirus; Eric S. Jones; Rex L. Baum; Jonathan W. Godt; Stephen Slaughter; Matthew M. Crawford; Jeremy Lancaster; Thomas Stanley; Dalia B. Kirschbaum; William J. Burns; Robert G. Schmitt; Kassandra O. Lindsey; et al. (Landslides, 2020)
Detailed information about landslide occurrence is the foundation for advancing process understanding, susceptibility mapping, and risk reduction. Despite the recent revolution in digital elevation data and remote sensing technologies, landslide mapping remains resource intensive. Consequently, a modern, comprehensive map of landslide occurrence across the United States (USA) has not been compiled. As a first step toward this goal, we present a national-scale compilation of existing, publicly available landslide inventories. This geodatabase can be downloaded in its entirety or viewed through an online, searchable map, with parsimonious attributes and direct links to the contributing sources with additional details. The mapped spatial pattern and concentration of landslides are consistent with prior characterization of susceptibility within the conterminous USA, with some notable exceptions on the West Coast. Although the database is evolving and known to be incomplete in many regions, it confirms that landslides do occur across the country, thus highlighting the importance of our national-scale assessment. The map illustrates regions where high-quality mapping has occurred and, in contrast, where additional resources could improve confidence in landslide characterization. For example, borders between states and other jurisdictions are quite apparent, indicating the variation in approaches to data collection by different agencies and disparity between the resources dedicated to landslide characterization. Further investigations are needed to better assess susceptibility and to determine whether regions with high relief and steep topography, but without mapped landslides, require further landslide inventory mapping. Overall, this map provides a new resource for accessing information about known landslides across the USA.

Ecological and genomic analyses of candidate phylum WPS ‐2 bacteria in an unvegetated soil - Andriy Sheremet; Gareth M. Jones; Jessica Jarett; Robert M. Bowers; Isaac Bedard; Cassandra Culham; Emiley A. Eloe‐Fadrosh; Natalia Ivanova; Rex R. Malmstrom; Stephen E. Grasby; Tanja Woyke; Peter F. Dunfield (Environmental Microbiology, 2020)
Summary Members of the bacterial candidate phylum WPS‐2 (or Eremiobacterota) are abundant in several dry, bare soil environments. In a bare soil deposited by an extinct iron–sulfur spring, we found that WPS‐2 comprised up to 24% of the bacterial community and up to 10 8 cells per g of soil based on 16S rRNA gene sequencing and quantification. A single genus‐level cluster ( Ca. Rubrimentiphilum) predominated in bare soils but was less abundant in adjacent forest. Nearly complete genomes of Ca. Rubrimentiphilum were recovered as single amplified genomes (SAGs) and metagenome‐assembled genomes (MAGs). Surprisingly, given the abundance of WPS‐2 in bare soils, the genomes did not indicate any capacity for autotrophy, phototrophy, or trace gas metabolism. Instead, they suggest a predominantly aerobic organoheterotrophic lifestyle, perhaps based on scavenging amino acids, nucleotides, and complex oligopeptides, along with lithotrophic capacity on thiosulfate. Network analyses of the entire community showed that some species of Chloroflexi , Actinobacteria , and candidate phylum AD3 (or Dormibacterota) co‐occurred with Ca. Rubrimentiphilum and may represent ecological or metabolic partners. We propose that Ca. Rubrimentiphilum act as efficient heterotrophic scavengers. Combined with previous studies, these data suggest that the phylum WPS‐2 includes bacteria with diverse metabolic capabilities.

Temperature-responsive PNDJ hydrogels provide high and sustained antimicrobial concentrations in surgical sites - Derek J. Overstreet; Vajra S. Badha; John M. Heffernan; Erin P. Childers; Rex C. Moore; Brent L. Vernon; Alex C. McLaren (Drug Delivery and Translational Research, 2019)

The Bacterial Symbiont Phaeobacter inhibens Shapes the Life History of Its Algal Host Emiliania huxleyi - Anna R. Bramucci; Leen Labeeuw; Fabini D. Orata; Elizabeth M. Ryan; Rex R. Malmstrom; Rebecca J. Case (Frontiers in Marine Science, 2018)

Alginic acid as immunostimulant: effects of dose and frequency on growth performance, immune responses, and white spot syndrome virus resistance in tiger shrimp Penaeus monodon (Fabricius, 1798) - Vianney T. Ojerio; Valeriano L. Corre; Nieves A. Toledo; Karen Grace S. Andrino-Felarca; Lovelyn Marie Nievales; Rex Ferdinand M. Traifalgar (Aquaculture International, 2018)

Cryptic genetic divergence in Scolopsis taenioptera (Perciformes: Nemipteridae) in the western Pacific Ocean - Ryo Kakioka; Nozomu Muto; Hirohiko Takeshima; Arnold C. Gaje; Ramon S. Cruz; Ulysses B. Alama; Armi May T. Guzman; Rex Ferdinand M. Traifalgar; Ricardo P. Babaran; Osman Muda; Wahidah Mohd Arshaad; Sukchai Arnupapboon; et al. (Ichthyological Research, 2018)

Rapid and cost-effective molecular identification of the three mackerel species of the genus Rastrelliger (Perciformes: Scombridae) using PCR-RFLP analysis - Nozomu Muto; Hirohiko Takeshima; Ryo Kakioka; Ulysses B. Alama; Armi May T. Guzman; Ramon S. Cruz; Arnold C. Gaje; Rex Ferdinand M. Traifalgar; Hiroyuki Motomura; Fumihito Muto; Ricardo P. Babaran; Satoshi Ishikawa (Marine Biodiversity, 2017)

Dietary Spirulina (Arthrospira platensis) replacement enhances performance of juvenile Nile tilapia (Oreochromis niloticus) - Stephanie F. Velasquez; Merab A. Chan; Rhea G. Abisado; Rex Ferdinand M. Traifalgar; Melchor M. Tayamen; Gian Carlo F. Maliwat; Janice A. Ragaza (Journal of Applied Phycology, 2016)

Genetic and morphological differences among the three species of the genus Rastrelliger (Perciformes: Scombridae) - Nozomu Muto; Ulysses B. Alama; Harutaka Hata; Armi May T. Guzman; Ramon Cruz; Arnold Gaje; Rex Ferdinand M. Traifalgar; Ryo Kakioka; Hirohiko Takeshima; Hiroyuki Motomura; Fumihito Muto; Ricardo P. Babaran; et al. (Ichthyological Research, 2016)

Molecular Detection of New Delhi Metallo-Beta-Lactamase-1 (NDM-1) Positive Bacteria from Environmental and Drinking Water Samples by Loop Mediated Isothermal Amplification of bla NDM-1 - P. Rathinasabapathi; Deepak S. Hiremath; Rex Arunraj; M. Parani (Indian Journal of Microbiology, 2015)

Emplacement of the Cabezo María lamproite volcano (Miocene, SE Spain) - Thomas M. Gernon; Samuel Spence; Clive N. Trueman; Rex N. Taylor; Eelco Rohling; Stuart J. Hatter; Ian C. Harding (Bulletin of Volcanology, 2015)

Gut microbiome composition and metabolomic profiles of wild western lowland gorillas ( Gorilla gorilla gorilla ) reflect host ecology - Andres Gomez; Klara Petrzelkova; Carl J. Yeoman; Klara Vlckova; Jakub Mrázek; Ingrid Koppova; Franck Carbonero; Alexander Ulanov; David Modry; Angelique Todd; Manolito Torralba; Karen E. Nelson; et al. (Molecular Ecology, 2015)
The metabolic activities of gut microbes significantly influence host physiology; thus, characterizing the forces that modulate this micro‐ecosystem is key to understanding mammalian biology and fitness. To investigate the gut microbiome of wild primates and determine how these microbial communities respond to the host's external environment, we characterized faecal bacterial communities and, for the first time, gut metabolomes of four wild lowland gorilla groups in the Dzanga‐Sangha Protected Areas, Central African Republic. Results show that geographical range may be an important modulator of the gut microbiomes and metabolomes of these gorilla groups. Distinctions seemed to relate to feeding behaviour, implying energy harvest through increased fruit consumption or fermentation of highly fibrous foods. These observations were supported by differential abundance of metabolites and bacterial taxa associated with the metabolism of cellulose, phenolics, organic acids, simple sugars, lipids and sterols between gorillas occupying different geographical ranges. Additionally, the gut microbiomes of a gorilla group under increased anthropogenic pressure could always be distinguished from that of all other groups. By characterizing the interplay between environment, behaviour, diet and symbiotic gut microbes, we present an alternative perspective on primate ecology and on the forces that shape the gut microbiomes of wild primates from an evolutionary context.

International STakeholder NETwork (ISTNET): creating a developmental neurotoxicity (DNT) testing road map for regulatory purposes - Anna Bal-Price; Kevin M. Crofton; Marcel Leist; Sandra Allen; Michael Arand; Timo Buetler; Nathalie Delrue; Rex E. FitzGerald; Thomas Hartung; Tuula Heinonen; Helena Hogberg; Susanne Hougaard Bennekou; et al. (Archives of Toxicology, 2015)

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

Genomewide predictions from maize single-cross data - Jon M. Massman; Andres Gordillo; Robenzon E. Lorenzana; Rex Bernardo (Theoretical and Applied Genetics, 2013)

Doubling the chromosome number of bahiagrass via tissue culture - Kenneth H. Quesenberry; Judith M. Dampier; Y. Y. Lee; Rex L. Smith; Carlos A. Acuña (Euphytica, 2010)

Primary peritoneal and ovarian cancers: an epidemiological comparative analysis - Delores J. Grant; Patricia G. Moorman; Lucy Akushevich; Rachel T. Palmieri; Rex C. Bentley; Joellen M. Schildkraut (Cancer Causes & Control, 2010)

Change in zooxanthellae and mucocyte tissue density as an adaptive response to environmental stress by the coral, Montastraea annularis - Alan M. Piggot; Bruce W. Fouke; Mayandi Sivaguru; Robert A. Sanford; H. Rex Gaskins (Marine Biology, 2009)

Understanding the relation between Arctic ozone loss and the volume of polar stratospheric clouds - N. R. P. Harris; R. Lehmann; M. Rex; P. Von Der Gathen (International Journal of Remote Sensing, 2009)

Spatiotemporal patterns of wetland occurrence in the Prairie Pothole Region of eastern South Dakota - Sharon N. Kahara; Rachel M. Mockler; Kenneth F. Higgins; Steven R. Chipps; Rex R. Johnson (Wetlands, 2009)

Structure–Activity Relationships and Organ Specificity in the Induction of GST and NQO1 by Alkyl-Aryl Isothiocyanates - Rex Munday; Yuesheng Zhang; Christine M. Munday; Meghana V. Bapardekar; Joseph D. Paonessa (Pharmaceutical Research, 2008)

Inferring the diversification of the epiphytic fern genus Serpocaulon (Polypodiaceae) in South America using chloroplast sequences and amplified fragment length polymorphisms - H.-P. Kreier; M. Rex; K. Weising; M. Kessler; A. R. Smith; H. Schneider (Plant Systematics and Evolution, 2008)

New evidence from a calcite-dolomite carbonatite dyke for the magmatic origin of the massive Bayan Obo ore-bearing dolomite marble, Inner Mongolia, China - M. J. Le Bas; Yang Xueming; Rex N. Taylor; B. Spiro; J. A. Milton; Zhang Peishan (Mineralogy and Petrology, 2007)

The guinea pig forced swim test as a new behavioral despair model to characterize potential antidepressants - Karsten M. Wicke; Andre Rex; Ana Jongen-Relo; Ilona Groth; Gerhard Gross (Psychopharmacology, 2007)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

International, open-label, noncomparative, clinical trial of micafungin alone and in combination for treatment of newly diagnosed and refractory candidemia - L. Ostrosky-Zeichner; D. Kontoyiannis; J. Raffalli; K. M. Mullane; J. Vazquez; E. J. Anaissie; J. Lipton; P. Jacobs; J. H. Jansen Rensburg; J. H. Rex; W. Lau; D. Facklam; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

International, open-label, noncomparative, clinical trial of micafungin alone and in combination for treatment of newly diagnosed and refractory candidemia - L. Ostrosky-Zeichner; D. Kontoyiannis; J. Raffalli; K. M. Mullane; J. Vazquez; E. J. Anaissie; J. Lipton; P. Jacobs; J. H. Jansen Rensburg; J. H. Rex; W. Lau; D. Facklam; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Anthropometric Measurements and Epithelial Ovarian Cancer Risk in African–American and White women - Cathrine Hoyo; Andrew Berchuck; Susan Halabi; Rex C. Bentley; Patricia Moorman; Brian Calingaert; Joellen M. Schildkraut (Cancer Causes & Control, 2005)

A Watershed-Scale Model for Predicting Nonpoint Pollution Risk in North Carolina - Kevin M. Potter; Frederick W. Cubbage; Gary B. Blank; Rex H. Schaberg (Environmental Management, 2004)

Voriconazole Salvage Treatment of Invasive Candidiasis - L. Ostrosky-Zeichner; A. M. L. Oude Lashof; B. J. Kullberg; J. H. Rex (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Expression Profile of the Channel Catfish Spleen: Analysis of Genes Involved in Immune Functions - Arif M. Kocabas; Ping Li; Dongfeng Cao; Attila Karsi; Chongbo He; Andrea Patterson; Zhenlin Ju; Rex A. Dunham; Zhanjiang Liu (Marine Biotechnology, 2002)

Extreme mitochondrial DNA divergence within populations of the deep-sea gastropod Frigidoalvania brychia - Quattro J.; Chase M.; Rex M.; Greig T.; Etter R. (Marine Biology, 2001)

The relationship between dissolved oxygen concentration and maximum size in deep-sea turrid gastropods: an application of quantile regression - McClain C.; Rex M. (Marine Biology, 2001)

A Comparison of Match Ozonesonde-Derived and 3D Model Ozone Loss Rates in the Arctic Polar Vortex during the Winters of 1994/95 and 1995/96 - I. Kilbane-Dawe; N. R. P. Harris; J. A. Pyle; M. Rex; A. M. Lee; M. P. Chipperfield (Journal of Atmospheric Chemistry, 2001)

Phylogenomic Analysis of the α Proteasome Gene Family from Early-Diverging Eukaryotes - Juan L. Bouzatrid="*"rid="†"; Leslie K. McNeilrid="*"; Hugh M. Robertson; Leellen F. Solter; Julie E. Nixon; Jonathan E. Beever; H. Rex Gaskins; Gary Olsen; Shankar Subramaniam; Mitchell L. Sogin; Harris A. Lewin (Journal of Molecular Evolution, 2000)

AC Stampede Russet: A high-yielding oblong russet cultivar for the french fry and fresh market industries - D. R. Lynch; J. C. Miller; L. M. Kawchuk; C. A. Schaupmeyer; J. Holley; J. Panford; D. K. Fujimoto; D. Waterer; J. Wahab; B. Rex; M. S. Goettel (American Journal of Potato Research, 2000)

Temporal distribution of waterfowl in eastern South Dakota: Implications for aerial surveys - David E. Naugle; Rex R. Johnson; Thomas R. Cooper; Matthew M. Holland; Kenneth F. Higgins (Wetlands, 2000)

Effect of air cavities on the dose delivered to the lung during high-dose brachytherapy - Richard M. Ambrosi; John I. W. Watterson; Tom Nam; Rex J. Keddy (Biological Trace Element Research, 1999)

Expression of chicken gizzard RLC complements the cytokinesis and developmental defects of Dictyostelium RLC null cells - Pengxin Chen; Bernard M. Chaudoir; Kathleen M. Trybus; Rex L. Chisholm (Journal of Muscle Research and Cell Motility, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Carbendazim-induced abnormal development of the acrosome during early phases of spermiogenesis in the rat testis - M. Nakai; Kiyotaka Toshimori; Kazuya Yoshinaga; Tetsuo Nasu; Rex A. Hess (Cell and Tissue Research, 1998)

Bathymetric patterns of genetic variation in a deep-sea protobranch bivalve, Deminucula atacellana - M. R. Chase; R. J. Etter; M. A. Rex; J. M. Quattro (Marine Biology, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

A Framework for Information Systems in Life‐Cycle‐Oriented Environmental Management - Teresa M. Shaft; Rex T. Ellington; Mark Meo; Mark P. Sharfman (Journal of Industrial Ecology, 1997)
Summary Although business firms have improved their environmental performance, a variety of forces are pushing businesses toward adopting environmental management throughout the entire life cycle of their products and processes. In this article we discuss the information systems elements of an environmental management approach we call “life‐cycle‐oriented environmental management” (LCOEM).This approach requires the firm to manage the effects of its processes from the creation of inputs to the final disposal of outputs, that is, from cradle to grave. We present a framework of the classes of information systems needed, describe their use in an LCOEM setting and define their inter relationships. We conclude with a discussion of the implications of LCOEM information systems.

Amisk: A clonal variant of Ranger Russet - D. R. Lynch; L. M. Kawchuk; C. A. Schaupmeyer; J. Holley; D. Waterer; B. L. Rex; M. K. Pritchard; J. Panford (American Journal of Potato Research, 1995)

AC Ptarmigan: An early maturing potato cultivar with good chipping and fresh market quality - D. R. Lynch; C. Schaupmeyer; L. M. Kawchuk; T. R. Tarn; B. Rex; J. Holley; D. Waterer; J. Panford; M. K. Pritchard (American Journal of Potato Research, 1994)

Association Business - David Curwen; Ronald Knight; Therese M. Work; Hugh J. Murphy; Pete Weingartner; John Ojala; Gary Franc; Roger Brook; Tom German; Sam Thorton; John Bamberg; John C. Wallace; et al. (American Journal of Potato Research, 1993)

The source of inulin in samples of vasa recta blood - Paul A. Johnston; Frank B. Lacy; Veeraf M. Sanjana; Channing R. Robertson; Rex L. Jamison (Annals of Biomedical Engineering, 1977)